USING DRTA (DIRECTED READING THINKING ACTIVITY) STRATEGY TO IMPROVE THE SECOND YEAR STUDENTS’ ABILITY IN COMPREHENDING NARRATIVE TEXTS AT SMA N 5 PEKANBARU - Ella Novi Anjani; Atni Prawati; Mahdum ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This classroom action research was aimed to find out if the Directed Reading Thinking Activitystrategy could improve the students’ ability in comprehending narrative texts of the second year students of SMAN5 Pekanbaru. The class XI IPA 7 became the subject of the research, the participants were 39.The data were collected by using of tests, observations, and field notes. The data were analyzed byquantitative data and qualitative data. The research finding showed that the implementation of Directed Reading Thinking Activitystrategy as the teaching strategy could improve students’ ability in comprehending narrative texts both at the first cycle and second cycle.It was also proved that applying the procedures of Directed Reading Thinking Activitystrategy in teaching reading could raise students’ predictions, before reading, during and after reading in comprehendings narrative text, and motivation to shared with their friends in groups.Keywords: Directed Reading Thinking Activity Strategy, Students’ Reading Ability, Comprehending Narrative Text